PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT, SUPPLY CHAIN MANAGEMENT, DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA OPERASI (Studi pada Pengrajin Tas di Sentra Industri Tas Ciampea, Kab. Bogor) - Labdhagati, Haifa; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2017)
The production processes are closely related to operations management. Operations management is the key driver of production processes, therefore, operational performance is fundamental for the sustainability of the company. Various production problems which encountered most of bags manufacturer in Ciampea, Bogor Regency, indicates the need for further study. This study purpose is to analyze the impact of Total Quality Management, Supply Chain Management, and entrepreneurial orientation on operational performance.Data collection technique used in this study are questionnaire. The sample is selected using simple random sampling technique and the number of respondents selected is 58 respondents. To analyze the impact of independent variables on dependent variable, multiple linier regression analysis is used.The result of this study showed that Total Quality Management have positive impact on operational performance (first hypothesis accepted). The second hypothesis which state that Supply Chain Management have positive impact on operational performance is accepted as well. The third hypothesis which state that entrepreneurial orientation have positive impact on operational performance is accepted. The coefficient of determination test result stated that all three independent variables have an impact of 53% on operational performance. Bag manufacturers in Ciampea, Bogor Regency are recommended to develop their employee, integrate with suppliers, and not too depend on intermediary traders.